Ecological View From The Perspective of Quranic Verses: Contesting the Idea of Religion and Environment - Muta Ali Arauf (International Journal of Social Science and Religion (IJSSR), 2021)
This research aims to know the relation between religion and environtment in a deep comprehensive understanding. How religion and environtment in some extents they are too related. In Islam for example, concept of shari’a seemingly agreed and supported the idea of nature and animal conservation. But, in some extent they are contradictive. This contradictive discouse could be seen from any kinds of texts of religious scriptures in how they deal with preservation of nature and animal (killing animal). The role of religious text we may say “yes” that it deal and closely related how the ecological views are constructed. How it overcomes the natural degradation, pollutions for instance. But, religion also should be understood as an orientation of the cosmos and how actually our human existence has an important role to the world. In broadest sense, we understand that religion also means of how people know the limits of reality and how humans interact with their own environment. Religion often talk about the cosmological stories, systems and symbols, ritual practices, norms and ethics, the history, and the institutional structure that transmits the view where human beings as an integral part in the world—and has a sense of responsibility towards nature. This article use the analytical approach in analyizing the issue of religion and environtment. Thus, the relation between Islamic law, Quranic verses and Shari’a are compactible in responding the issue of environtment